2018
DOI: 10.1017/s1460396918000353
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative endometrial cancer treatments with electronic brachytherapy source

Abstract: PurposeThis study is a dosimetric and acute toxicity comparison of endometrial cancer patients treated with either Axxent (Xoft, Inc., San José, CA, USA) electronic and interstitial brachytherapy versus interstitial high dose rate brachytherapy (HDRBT).Materials and MethodsBetween 2015 and 2017, 94 patients with postoperative endometrial cancer were treated in our centre with the Axxent electronic brachytherapy (eBT) system. The V150 and V200 are evaluated prospectively for each plan. The mean age of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The eBT device is a useful addition in centers with an HDR device. Its mobility and versatility mean that it can be used as a complementary facility to treat cervical cancer and for intraoperative radiotherapy in breast cancer, in skin cancer, and in postoperative treatment of endometrial cancer …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The eBT device is a useful addition in centers with an HDR device. Its mobility and versatility mean that it can be used as a complementary facility to treat cervical cancer and for intraoperative radiotherapy in breast cancer, in skin cancer, and in postoperative treatment of endometrial cancer …”
Section: Resultsmentioning
confidence: 99%
“…In our study, we did not modify treatment owing to differences in RBE with respect to Ir192 because of the good results achieved with treatment administered to the endometrium and the contradictory results reported in several published studies. Modification of the prescribed dose continues to be controversial in low‐energy cases …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicity was scored according to Radiation Therapy Oncology Group — European Organization for Research and Treatment of Cancer (RTOG-EORTC). There was 1 (1.1%) acute G2 event and 1 month after treatment there were none [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modification of the prescribed dose continues to be controversial in lowenergy cases ( 32 ). We based our approach on previous experience in that the prescription dose was not modified owing to differences in RBE with respect to 192 Ir, and good results were obtained with eBT in endometrium ( 33 ) and cervical cancer ( 19 ). Similarly, a clinical study showed that modifying the prescription dose by including the RBE factor for treatment of nodular and superficial basal cell carcinoma using eBT reduced the control of the tumor from 95%-90% ( 34 ).…”
Section: Article In Pressmentioning
confidence: 99%